Analysis of Balancing Methods of Measurement of Small Resistance Changes - Masiulionis, R.; Kvedaras, V.; Kvedaras, R. (Elektronika ir Elektrotechnika, 2011)
Methods of measurement of small resistance changes by using digitally balanced Wheatstone bridge and digitally balancing currents are analysed in the paper. Equations for resistance change measurement code are obtained for Wheatstone bridge using regulated resistance connected in parallel to bridge resistance as well as for measurements using digitally regulated current source. It is shown that using regulation on the passive side of the circuit is more preferred because linear simple dependencies of the measured resistance change to the resulting code are obtained in these cases. New serial method of digital balancing of currents is proposed and investigated. It is shown that this method has more advantages compared to using two current sources. Ill. 3, bibl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.683